Formulasi dan Evaluasi Sediaan Obat Kumur (Mouthwash) dari Ekstrak Etanol Daun Kalangkala (Litsea angulata) sebagai Antiseptik Mulut - Rohama Rohama; Melviani Melviani (Jurnal Surya Medika (JSM), 2021)
Research of mouthwash formulation and evaluation of kalangkala leaves extract (Litsea angulata) as an oral antiseptic also has been tested in Streptococcus mutans bacteria by variation in the concentration of extract 2%, 2,5%, and 3%, which aims to determine the ideal formula in physical quality and has the highest antibacterial activity based on an inhibition zone of Streptococcus mutans bacteria in mouthwash formula. The methods used include the step of extraction of Kalangkala leaves, preparation of mouthwash with 3 formula F1 (2%), F2 (2,5%), and F3 (3%) followed by an evaluation that includes organoleptic, pH test, viscosity test, and the test of inhibition zone bacteria. The test of inhibition zone bacteria used NA media with diffusion method. Stability was performed on weeks 1, 2, 3, and 4. The result showed variation in the concentration of extract kalangkala leaves in a mouthwash formula affects the diameter of the inhibition zone. But did not have a significant effect on the physical stability properties of the mouthwash formula. Mouthwash formula has the highest antibacterial activity based on the inhibition zone of Streptococcus mutans that is 3% contained in formula F3.